Antibacterial Activity of 04 Medicinal Plant on the IN VITRO Growth of Multi-Resistant Strains Involved in Diarrhea in the Department of Kouto (Ivory Coast) - Monon, Kone; Abdoulaye, Toure; Eric-Kevin, Bolou Gbouhoury; Abou, Ouattara; Karamoko, Ouattara; Adama, Coulibaly (European Scientific Journal, ESJ, 2019)
This work aims at evaluating in vitro the antibacterial effects of aqueous and hydroethanolic extracts of leaf macerates, Manilkara multinervis, Waltheria indica root bark, Securrinega virosa, and Anogeissus leiocarpa stem bark. These four medicinal plants are traditionally used to treat diarrhea in the canton of North-Niéné (Department of Kouto, Côte d’Ivoire). The antibacterial activities of the various extracts from these plants were carried out on multi-resistant strains (Escherichia coli BLSE, Shigella flexneri BLSE, Staphylococcus aureus meti-R). The methodology consisted of extracting the drugs with a 70% hydroalcoholic solvent and distilled water. Agar diffusion and dilution methods were used for susceptibility testing and determination of CMI and CMB parameters. Agar diffusion and dilution methods were used. By the diffusion method, all four plants were found to be active on at least one of the bacteria tested. The ethanolic extract of M. Multinervis was the most active by inducing a diameter of 15 mm on the growth of S. aureus meti-R. As for the dilution method, the ethanolic extracts of W. indica and M. Multinervis showed bactericidal effects on both S. aureus at 6.25 mg/mL and 3.125 mg/mLrespectively as well as on all other 100 mg/mL germs. Only M. Multinervis recorded the highest activity. This important activity was demonstrated on S. aureus meti-R with a minimum bactericidal concentration of 3.125 mg/mL. These results confirm the traditional use of these plants in the management of diarrheal diseases in the Department of Kouto.